ETHNICITY AND ISLAMIC ACTIVISM IN DIASPORA - Abdul Wahid Hasyim (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2020)
This article examines the “urang awak”, a term referring to the Minangnese who trace their origin to Minangkabau in West Sumatera , and their dakwah activism in diaspora. It problematises the relation of Islam activism and ethnic identity of a diasporic community in contemporary West-Java, Indonesia. It further argues that mosque has been central to the activities of dakwah activism of the urang awak in diaspora. As this article demonstrates, the Harakatul Jannah Mosque and Al-Anwar Mosque reserve as important bases for dakwah activism of urang awak in a dominant culture of Sundanese and Javanese. Through these mosques, the urang awak attempt to preserve their ethnic identity, mainly expressed through the mosques’ architecture, language, and religious activities that clearly symbolise the identity of urang awak.